Trade-offs? Unveiling the interrelationships between urban ecosystem services and public services in heterogeneous landscapes - Qian Cao; Jian-Jin Liang; Xue-Ning Fang; Jian-Min Qiao; Jing Wu (Ecological Indicators, 2025)
Urban ecosystem services (UESs) and urban public services (UPSs) play pivotal roles in advancing urban sustainability. However, the intricate interrelationships between UESs and UPSs within urban contexts remain underexplored. This study addressed this gap by first investigating the spatiotemporal dynamics of UESs driven by urban landscape transformations and subsequently exploring the complex interrelationships between UESs and UPSs in a dynamic urban center characterized by heterogeneous landscapes. From 2013 to 2019, urban landscape transformations led to significant spatial alterations to the UESs. However, the regional mean UESs showed minimal changes owing to a slight increase in urban tees. Strong synergies were found between the UESs, but the strength of the correlation varied across different service pairs. Through the co-occurrence analysis, four UESs bundles were identified, each corresponding to particular land cover types with distinct UESs provision levels. The bivariate spatial correlation analysis revealed distinct patterns in the relationships between the UESs and UPSs. A high-high cluster was identified within and adjacent to a national park. The high-low clusters were primarily found in residential zones while the low–high clusters appeared in commercial streets. The UESs supply demonstrated a nonlinear relationship with the UPSs provision, characterized by an initial decline followed by a subsequent increase as the availability of UPSs increased. This demonstrated the possibility of achieving synergies between UESs and UPSs during the advanced phases of urbanization. The research findings offer practical implications for urban ecosystem management and planning to enhance UESs provision and foster synergetic interactions between UESs and UPSs.